Gas identification with graphene plasmons - Hai Hu (Nature Portfolio, 2019)
Identification of gas molecules is crucial in healthcare and security applications. Here the authors achieve label-free identification of SO2, NO2, N2O, and NO gas molecules by detecting their rotational-vibrational modes using graphene nanoribbon plasmons.